Augmented BIB Design-An Alternative Statistical Design in Germplasm Evaluation Trials - R Venugopalan (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2008)
Randomized Block Design (RBD) is commonly employed to evaluate a set of germplasm accessions (test treatments) along with local checks. In such a trial, if the test treatments under evaluation are more in number and the availability of the seeds is limited, then an alternate experimental design has to be employed. As a remedy, Balanced Incomplete Block Design (BIBD), which estimates treatments contrasts with more precision and the treatments are not repeated in all the blocks, unlike RBD, may be used. Such a constructed layout, not only saves the precious seed material of the test treatments, but also directly reduces the cost of all the related inputs such as labour, water, fertilizers, pesticides etc. Foregoing thoughts were elucidated in the evaluation of 100 accessions of okra along with four check varieties (Arka Anamika, Arka Abhay, Parbhani Kranti and PB-7) evaluated using Augmented BIB Design with six blocks in the Division of Vegetable crops at I.I.H.R., Bangalore during Kharif 2005. Results showed that by adopting BIB experimental design, instead of regular complete block design 60.2% of the land area required for conducting germplasm evaluation in Okra had been reduced.